Discovery, X-ray structure and CPP-conjugation enabled uptake of p53/MDM2 macrocyclic peptide inhibitors. Issue 6 (16th September 2021) - Schneider, Anselm F. L.; Kallen, Joerg; Ottl, Johannes; Reid, Patrick C.; Ripoche, Sebastien; Ruetz, Stephan; Stachyra, Therese-Marie; Hintermann, Samuel; Dumelin, Christoph E.; Hackenberger, Christian P. R.; Marzinzik, Andreas L.
Abstract : mRNA display leads to the identification of a macrocyclic peptide inhibitor with a unique binding mode to MDM2, a negative regulator of the tumor suppressor p53 . Conjugation to a cell-penetrating peptide allows in cellulo evaluation of inhibition. Abstract : Mouse double minute 2 homolog (MDM2, Hdm2) is an important negative regulator of the tumor suppressor p53 . Using a mRNA based display technique to screen a library of >10 12 in vitro -translated cyclic peptides, we have identified a macrocyclic ligand that shows picomolar potency on MDM2 . X-Ray crystallography reveals a novel binding mode utilizing a unique pharmacophore to occupy the Phe/Trp/Leu pockets on MDM2 . Conjugation of a cyclic cell-penetrating peptide (cCPP) to the initially non cell-permeable ligand enables cellular uptake and a pharmacodynamic response in SJSA-1 cells. The demonstrated enhanced intracellular availability of cyclic peptides that are identified by a display technology exemplifies a process for the application of intracellular tools for drug discovery projects.